Enhancing Vigor and Viability of Deteriorated True Shallot Seed by Matriconditioning Using Biofertilizer and Washed Rice Water - Saputra , Muhamad Wahyu; Sari , Vega Kartika; Slameto, Slameto; Setiawati , Tri Candra; Wafa , Ali; Firmansyah, Toni; Sundahri , Sundahri (Journal of Applied Agricultural Science and Technology, 2024)
True Shallot Seed (TSS) is a healthy, cost-effective, and high-yielding alternative to shallot bulbs. However, TSS has a short shelf life due to deterioration during storage. Viability and vigor of deteriorated seed can be enhanced using Plant Growth Promoting Rhizobacteria (PGPR). Washed rice water contains macro and micronutrients that also support metabolic processes and improve the accumulation of seed nutrients during germination. Therefore, this study aimed to investigate the role of matriconditioning with a mixture of PGPR and rice washing water in enhancing shallot seed vigor and viability. Shallot seed used in the study decreased physiological quality with 9.09% moisture and 52.25% germination. Matriconditioning had 5 treatments, namely Control (M0), Matriconditioning without PGPR (M1), Matriconditioning plus PGPR RhizomaX (M2), Matriconditioning plus PGPR BenprimA (M3), and Matriconditioning plus PGPR FloraOne (M4). Washed rice water had 3 levels, namely Control (A0), 50% concentration (A1), and 100% concentration (A2). Other variables examined in this study included germination rate, maximum growth potential, relative growth rate, uniformity, and vigor index. Data were analyzed using Analysis of Variance (ANOVA), and Duncan test was applied for significant results at the 5% level. The results showed that matriconditioning using a mixture of rice husk charcoal and PGPR RhizomaX (M2) produced enhanced vigor and viability of deteriorated shallot seed. The application of leachate water for 5 days during germination, specifically at a concentration of 100% (A2), significantly improved vigor and viability. Finally, the interaction between treatment M2A2 had the best vigor and viability among all other treatments.